Handbook of advanced magnetic materials - Liu, Yi, 1967-; Shindō, D. (Daisuke), 1953-; Sellmyer, David J. (Springer ; Tsinghua University Press, 2006)
From high-capacity, inexpensive hard drives to mag-lev trains, recent achievements in magnetic materials research have made the dreams of a few decades ago reality. The objective of Handbook of Advanced Magnetic Materials is to provide a timely, comprehensive review of recent progress in magnetic materials research. This broad yet detailed reference consists of four volumes: